Daniel's mysticism of resistance in its Seleucid context - Seals, Timothy L. (Lexington Books/Fortress Academic, 2022)
The prophet Daniel practiced a mysticism that was resistant to the repressive measures of Antiochus IV in 167 BCE. In this book, Timothy L. Seals argues for a postcolonial interpretation of Daniel that can serve as a spiritual resource in the on-going process of the decolonization of the world and hearts.